EARLY-MIDDLE ARCHAEAN CRUSTAL EVOLUTION DEDUCED FROM LU-HF AND U-PB ISOTOPIC STUDIES OF SINGLE ZIRCON GRAINS - Amelin Y.; Lee D.C.; Halliday A.N. (My University, 2000)
We report detailed high precision combined single grain U-Pb and Lu-Hf studies of early zircons to obtain more reliable indications of the extent of mantle depletion and crustal recycling in the Archean. Despite the possibility that MC-ICPMS affords for precise Hf isotopic measurement of single zircons, the complexity of grain populations adds uncertainty to initial isotopic ratios. Multiple episodes of zircon growth and ancient Pb loss, common in early Archaean rocks, result in 207Pb/206Pb ages, and in some cases 176Hf/176Hf ratios, that are variable between and within zircon grains. In order to evaluate the role of heterogeneity of zircon populations and to obtain the most reliable εHf(T), we have analysed several abraded zircon grains (from two to eleven) from each of several samples for both Lu-Hf and U-Pb. Hf isotopic analyses with precision better than 1 to 1.5 ε-units (2σ) were obtained from grains weighing between 3 and 10 micrograms. The observed internal variations in age, U-Pb discordance, and Hf isotopic composition have been tested against models of disturbance of isotopic systems in zircon. Application of the U-Pb and Lu-Hf methods to the same zircon grains and analysis of single grains appears to be crucial for finding closed geochemical systems and thereby obtaining reliable Hf isotope data from early Archaean rocks. The precision and accuracy of Hf isotopic data obtained with the approach presented here are limited mainly by the sensitivity of Hf isotopic analyses, and may be greatly improved with the progress of analytical techniques.
Keywords: Archaean; Precambrian::Archean; Докембрий::Архей